A method to rescale experimental data with dependence on Q2 for DVCS process - Giacinto Ciappetta (Results in Physics, 2014)
We analyze the procedure for rescaling the DVCS cross section data collected with different invariant mass, W, of the virtual photon–proton system. We suggest a method which makes the rescaling more functional to conduct statistical analysis on overall data. The study can be applied to rescale data collected with different photon virtuality Q2. We also show a dependence on Q2 for the δ parameter used to describe the cross section as a function of W.